Experimental Assessment of Intestinal Damage in Controlled Donation After Circulatory Death for Visceral Transplantation - Stringa, Pablo Luis (2023)
There is an urgent need to address the shortage of potential multivisceral grafts in order to reduce the average time in waiting list. Since donation after circulatory death (DCD) has been successfully employed for other solid organs, a thorough evaluation of the use of intestinal grafts from DCD is warranted. Here, we have generated a model of Maastricht III DCD in rodents, focusing on the viability of intestinal and multivisceral grafts at five (DCD5) and twenty (DCD20) minutes of cardiac arrest compared to living and brain death donors. DCD groups exhibited time-dependent damage. DCD20 generated substantial intestinal mucosal injury and decreased number of Goblet cells whereas grafts from DCD5 closely resemble those of brain death and living donors groups in terms intestinal morphology, expression of tight junction proteins and number of Paneth and Globet cells. Upon transplantation, intestines from DCD5 showed increased ischemia/reperfusion damage compared to living donor grafts, however mucosal integrity was recovered 48 h after transplantation. No differences in terms of graft rejection, gene expression and absorptive function between DCD5 and living donor were observed at 7 post-transplant days. Collectively, our results highlight DCD as a possible strategy to increase multivisceral donation and transplantation procedures.